Kinetics of Cytotoxic Lymphocytes Reconstitution after Induction Chemotherapy in Elderly AML Patients Reveals Progressive Recovery of Normal Phenotypic and Functional Features in NK Cells - Rey, Jérôme; Fauriat, Cyril; Kochbati, Eloïse; Orlanducci, Florence; Charbonnier, Aude; D’Incan, Evelyne; Andre, Pascale; Romagne, François; Barbarat, Bernadette; Vey, Norbert; Olive, Daniel (Frontiers in Immunology, 2017)
NK cells are defective in acute myeloid Leukemia (AML) at diagnosis. Here we studied the kinetic of expression of the major activating and inhibitory receptors of NK, CD8 T and γδ T cells in patients undergoing chemotherapy (CT) for the treatment of AML (n=29). We show that NK cells are the main affected population at diagnosis and that expression of activating receptors is partially restored within a few weeks after CT. CD8 T cells and γδ T cells are only weakly affected at diagnosis. KIR expression by NK cells, but not NKG2A and CD85j, was down regulated. Interestingly, the development of NK cells appeared altered as the most immature CD56bright NK cells were seriously under represented. Finally, we showed that NK cells functions were only partially restored 6 weeks after CT as degranulation capabilities of NK cells recovered whereas cytokine production remained low. Our data point out NK cells as anti-tumor effectors peculiarly hampered by leukemic cells. This study may indicate a timeline when NK-mediated therapies or other immunotherapies could be performed, particularly for patients excluded of hematopoietic stem cell transplantation.